Evaluation of passive microwave brightness temperature simulations and snow water equivalent retrievals through a winter season - Derksen, Chris; Toose, Peter; Lemmetyinen, Juha; Pulliainen, Jouni; Langlois, Alexandre; Rutter, Nick; Fuller, Mark (Remote Sensing of Environment, 2012)
Plot-scale brightness temperature (TB) measurements at 6.9, 19, 37, and 89 GHz were acquired in forest, open, and lake environments near Churchill,Manitoba, Canada with mobile sled-based microwave radiometers during the 2009–2010 winter season. Detailed physical snow measurements within the radiometer footprints were made to relate the microwave signatures to the seasonal evolution of the snowpack, and provide inputs for model simulations with the Helsinki University of Technology (HUT) snow emission model. Large differences in depth, density, and grain size were observed between the three land cover types. Plot-scale simulations with the HUT model showed a wide range in simulation accuracy between sites and frequencies. In general, model performance degradedwhen the effective grain size exceeded 2 mmand/or there was an ice lens present in the pack. HUTmodel performance improvedwhen simulationswere run regionally at the satellite scale (using three proportional land cover tiles: open, forest, and lake) and compared to Advanced Microwave Scanning Radiometer (AMSR-E) measurements. Root mean square error (RMSE) values ranged from approximately 4 to 16 K depending on the frequency, polarization, and land cover composition of the grid cell. Snow water equivalent (SWE) retrievals produced using forward TB simulations with the HUT model in combination with AMSR-E measurements produced RMSE values below 25 mm for the intensive study area. Retrieval errors exceeded 50 mm when the scheme was applied regionally.